2015
DOI: 10.1063/1.4915513
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated graphene field-effect transistors for air stable operation

Abstract: In this work, we report the fabrication of encapsulated graphene field effects transistors (GFETs) with excellent air stability operation in ambient environment. Graphene's 2D nature makes its electronics properties very sensitive to the surrounding environment, and thus, non-encapsulated graphene devices show extensive vulnerability due to unintentional hole doping from the presence of water molecules and oxygen limiting their performance and use in real world applications. Encapsulating GFETs with a thin lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…. Further experiments are necessary to fully clarify this dynamics and the interplay between specific molecules composing air atmosphere and oxygen molecules trapped on Gr or SiO 2 , it can be suggested that moisture could play a significant role in this context as it was found that water molecules could affect the doping .…”
Section: Resultsmentioning
confidence: 99%
“…. Further experiments are necessary to fully clarify this dynamics and the interplay between specific molecules composing air atmosphere and oxygen molecules trapped on Gr or SiO 2 , it can be suggested that moisture could play a significant role in this context as it was found that water molecules could affect the doping .…”
Section: Resultsmentioning
confidence: 99%
“…Materials selection and transistor design are highly influential in determining the stability of an EGFET. Many approaches have been used for improving the stability of TFTs so far: the addition of additives [68], fine-tuning the composition of a component [113], encapsulation [114], barriers [51], or modification of the transistor geometry [115]. Further exploration is needed, especially to control the temperature, humidity, and electrochemical stability of EGFETs.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is similar to oxygen doping of organic semiconductors [ 36 , 37 ], and this tendency explains the deviation of the minimum conductance point in many graphene FETs from zero V G . An effective encapsulation can minimize further air-induced doping and shift of transfer curves [ 38 ]. On the other hand, Giovannetti et al theoretically verified the charge-transfer doping of graphene by metal contacts, which can be regarded as another common source of unintentional doping in working devices [ 39 ].…”
Section: Basic Conceptsmentioning
confidence: 99%